Extensive TDDFT Benchmark Study of the Resonance Raman Spectra of Lumiflavin - Andrikopoulos, Prokopis C (Journal of computational chemistry, 2025)
© 2025 The Author(s). Journal of Computational Chemistry published by Wiley Periodicals LLC.